2021
DOI: 10.1108/ijbm-07-2020-0395
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of bank branch location in India: an empirical investigation

Abstract: PurposeBank branching plays a significant role in a wide range of economic activities. Existing studies on determinants of bank branching activities largely focus on developed countries; studies devoted to developing countries are scant. The purpose of this paper is to examine the determinants of bank branching activities in one of the largest developing country India.Design/methodology/approachThe authors employ a unique longitudinal data to study the determinants of bank branch location in India. These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…Other studies have also shown that, unlike common perception, public banks like private banks prefer locating their branches in high-income developed areas (Zhang et al, 2021). failure in financial sector and finance socially valuable projects in less developed regions and rural areas (Yeyati et al, 2005).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Other studies have also shown that, unlike common perception, public banks like private banks prefer locating their branches in high-income developed areas (Zhang et al, 2021). failure in financial sector and finance socially valuable projects in less developed regions and rural areas (Yeyati et al, 2005).…”
Section: Resultsmentioning
confidence: 97%
“…Zhang et al . (2021) too found that region specific factors influence the location of bank branches in India.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations